Ways of Expressing Certainty as a Variety of Epistemic Modality - Kosenko, Anna; Bezhenar, Iryna (My University, 2023)
The article deals ways of expressing certainty as a variety of epistemic modality. The research has proved that certainty is viewed as a type of subjective information available in texts and a form of epistemic modality expressed through explicitly-coded linguistic means.
Keywords: certainty, epistemic modality, evidentiality, hedge, assessment.